METODE MENDIDIK ANAK TANPA KEKERASAN DALAM PERSPEKTIF ISLAM - Lis Yulianti Syafrida Siregar (IAIN Padangsidimpuan, 2021)
As entrusted by Allah, children are the responsibility of parents who must be educated in Islam in order to be the savior of parents in life in this world and in the hereafter. However, in practice, not all parents understand how to educate their children properly. Parents' mistakes in choosing the method of educating children can have a negative impact on the psychological development and personality of the child. Islam provides guidance to educate children through several methods, namely the Al-quran dialogue method, the Al-quran narrative method, exemplary methods, practice and deed methods, ibrah and mau'izzah methods, as well as targhib and tarhib methods. Finally, the choice of method used is left up to the ability of parents to apply it and pay attention to the child's condition. The choice of one method or the use of a combination of methods is a parent's discretion which does not need to be doubted on its effectiveness because the source of this method is the Al-Quran and the hadith of the Prophet Muhammad.Keywords: Method, Educate Children, IslamAbstrakSebagai titipan Allah, anak merupakan tanggung jawab orang tua yang harus didik secara Islam agar dapat menjadi penyelamat orang tua dalam kehidupan di dunia maupun di akhirat. Namun dalam praktiknya tidak semua orang tua memahami bagaimana cara mendidik anak yang baik. Kesalahan orang tua memilih metode mendidik anak dapat berdampak buruk terhadap tumbuh kembang kejiwaan dan kepribadian anak. Islam memberi tuntunan mendidik anak melalui beberapa metode, yaitu metode dialog Al-qur’an, metode kisah Al-qur’an, metode keteladanan, metode praktik dan perbuatan, metode ibrah dan mau’izzah, serta metode targhib dan tarhib.Akhirnya, pemilihan metode yang digunakan diserahkan kepada kemampuan orang tua menerapkannya serta memperhatikan kondisi anak.Pemilihan satu metode ataupun penggunaan kombinasi metode merupakan diskresi orang tua yang tidak perlu diragukan lagi efektivitasnya karena metode tersebut sumbernya adalah Al-quran dan hadist Rasulullah SAW.